Central Nervous System Correlates of "Objective" Neuropathy in Alcohol Use Disorder. (23rd August 2019) - Zahr, Natalie M.; Pohl, Kilian M.; Pfefferbaum, Adolf; Sullivan, Edith V.
Abstract : Background: Among the neurological consequences of alcoholism is peripheral neuropathy. Relative to human immunodeficiency virus (HIV) or diabetes‐related neuropathies, neuropathy associated with alcohol use disorders (AUD) is understudied. In both the diabetes and HIV literature, emerging evidence supports a central nervous system (CNS) component to peripheral neuropathy. Methods: In seeking a central substrate for AUD‐related neuropathy, the current study was conducted in 154 individuals with AUD (43 women, age 21 to 74 years) and 99 healthy controls (41 women, age 21 to 77 years) and explored subjective symptoms (self‐report) and objective signs (perception of vibration, deep tendon ankle reflex, position sense, 2‐point discrimination) of neuropathy separately. In addition to regional brain volumes, risk factors for AUD‐related neuropathy, including age, sex, total lifetime ethanol consumed, nutritional indices (i.e., thiamine, folate), and measures of liver integrity (i.e., γ ‐glutamyltransferase), were evaluated. Results: The AUD group described more subjective symptoms of neuropathy and was more frequently impaired on bilateral perception of vibration. From 5 correlates, the number of AUD‐related seizures was most significantly associated with subjective symptoms of neuropathy. There were 15 correlates of impaired perception of vibration among the AUD participants: Of these, age and volume of frontal precentral cortex were the most robust predictors. Conclusions: This study supports CNS involvement in objective signs of neuropathy in AUD. Abstract : Peripheral neuropathies associated with Alcohol Use Disorders (AUD) ‐ relative to those associated with HIV or diabetes ‐ are understudied. Subjective and "objective" measures [perception of vibration, position sense, deep tendon ankle reflex, 2‐point discrimination] of peripheral neuropathy were evaluated in 154 individuals with AUD and 99 healthy controls aged 50 years. Among 15 correlates of impaired perception of vibration in the AUD participants, age and volume of frontal precentral cortex were the most robust predictors.